2003
DOI: 10.1080/15438600490424569
|View full text |Cite
|
Sign up to set email alerts
|

C‐peptide and Retinal Microangiopathy in Diabetes

Abstract: Increased extracellular matrix (ECM) protein deposition and capillary basement membrane (BM) thickening are characteristic features of diabetic retinal microangiopathy. Recent observations in the authors' laboratories suggest that high glucose in endothelial cells as well as diabetes causes up-regulation of total fibronectin (FN), as well as extradomain-B (EDB) containing the spliced variant of FN, oncofetal FN, in the retina. This splice variant is normally absent in mature adult tissues and is believed to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…C-peptide increases eNOS and NO activity (Johansson et al 2003; Tsimaratos et al 2003; Walcher et al 2004; Maezawa et al 2006). In smooth muscle cells (Chakrabarti et al 2004) and aortic endothelial cells (Young et al 2000; Tsimaratos et al 2003), C-peptide has been shown to increase intracellular Ca 2+ , thereby inducing NO production by endothelial NOS (eNOS) and iNOS, causing an NO-dependent vasodilation. In myocardial ischemia-reperfusion, C-peptide has been shown to exert cardioprotective effects through the release of NO (Young et al 2000).…”
Section: Immunoregulatory Effects Of C-peptidementioning
confidence: 99%
See 2 more Smart Citations
“…C-peptide increases eNOS and NO activity (Johansson et al 2003; Tsimaratos et al 2003; Walcher et al 2004; Maezawa et al 2006). In smooth muscle cells (Chakrabarti et al 2004) and aortic endothelial cells (Young et al 2000; Tsimaratos et al 2003), C-peptide has been shown to increase intracellular Ca 2+ , thereby inducing NO production by endothelial NOS (eNOS) and iNOS, causing an NO-dependent vasodilation. In myocardial ischemia-reperfusion, C-peptide has been shown to exert cardioprotective effects through the release of NO (Young et al 2000).…”
Section: Immunoregulatory Effects Of C-peptidementioning
confidence: 99%
“…It has been suggested that C-peptide has effects on angiogenesis (Chakrabarti et al 2004). There are indications that diabetes induces the up-regulation of oncofetal fibronectin in the retina (Khan et al 2004), a substance believed to be involved in angiogenesis and normally not found in mature tissue (Castellani et al 1994; Karelina and Eisen 1998).…”
Section: C-peptide-induced Effects On Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, when insulin production is impaired as in type 1 diabetes, C‐peptide secretion is also affected. With time, type 1 diabetic patients develop complications including atherosclerosis, nephropathy, retinopathy, and neuropathy 1–5. Administration of exogenous C‐peptide to type 1 diabetic patients has been shown to exert beneficial effects in many tissues affected by microvascular complications 6.…”
Section: Introductionmentioning
confidence: 99%
“…When, as in type 1 diabetes and late type 2 diabetes, insulin synthesis is impaired, synthesis of C-peptide is similarly impaired. Exogenous C-peptide has been shown to improve the function of many tissues commonly affected by diabetes complications (Lindstrom et al 1996; Johansson et al 2000; Chakrabarti et al 2004; Sima and Li 2006), a development supported by the fact that pancreatic and islet of Langerhans transplantation, restoring not only insulin secretion, but also secretion of C-peptide, will prevent and even reverse diabetic complications (Fiorina et al 2003a, 2003b, 2005a, 2005b; Lee et al 2006; Venturini et al 2006). Hence, C-peptide deficiency has successively emerged as a possible mechanism for the development of the disproportionate burden of complications affecting insulinopenic diabetes patients.…”
Section: Introductionmentioning
confidence: 99%